Seven-Channel Polyethersulfone Hollow-Fiber Membrane Preparation with Vapor-Induced Phase Separation - Xiaoyao Wang; Zhiyuan Hao; Rui Huang; Yajing Huang; Huiqun Zhang; Xiujuan Hao (Membranes)
Polyethersulfone (PES) has been widely used to fabricate hollow-fiber ultrafiltration membranes due to its good oxidative, thermal, and hydrolytic stability. Typical PES hollow-fiber membranes with a single bore have limited strength and may break under uneven pressure and vibration during membrane backwashing. Multi-channel hollow-fiber membranes have stronger breaking force due to their larger cross-sectional area, but fabricating them remains challenging due to the difficulty in controlling the phase inversion process. This study uses the vapor-induced phase separation (VIPS) method to fabricate a seven-channel PES hollow-fiber membrane, and the air gap and air relative humidity can help in membrane morphology control. Moreover, carboxylic graphene quantum dots (CGQDs) are first used in ultrafiltration membranes to increase membrane porosity and hydrophilicity. We found that the membrane prepared with a 7.5% CGQD mass fraction, a 10 cm air gap, and 99% relative humidity had the highest flux and porosity; the membrane pore size distribution was concentrated at 72 nm, and the pure water flux could reach 464 L·m−2 h−1·bar−1. In the long-term filtration performance test, the membrane can reject more than about 15% TOC and 84% turbidity at 50 L·m−2 h−1 flux, confirming its stability for water purification applications.